Calcium and Potassium Channels in Experimental Subarachnoid Hemorrhage and Transient Global Ischemia - Marcel A. Kamp; Maxine Dibué; Toni Schneider; Hans-Jakob Steiger; Daniel Hänggi (Stroke Research and Treatment)
Healthy cerebrovascular myocytes express members of several different ion channel families which regulate resting membrane potential, vascular diameter, and vascular tone and are involved in cerebral autoregulation. In animal models, in response to subarachnoid blood, a dynamic transition of ion channel expression and function is initiated, with acute and long-term effects differing from each other. Initial hypoperfusion after exposure of cerebral vessels to oxyhemoglobin correlates with a suppression of voltage-gated potassium channel activity, whereas delayed cerebral vasospasm involves changes in other potassium channel and voltage-gated calcium channels expression and function. Furthermore, expression patterns and function of ion channels appear to differ between main and small peripheral vessels, which may be key in understanding mechanisms behind subarachnoid hemorrhage-induced vasospasm. Here, changes in calcium and potassium channel expression and function in animal models of subarachnoid hemorrhage and transient global ischemia are systematically reviewed and their clinical significance discussed.